2010
DOI: 10.3989/gya.074908
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Properties, Microbiological Quality and Sensory Evaluation of Chicken and Duck Liver Paste (foie gras)

Abstract: Liver paste or foie gras, which is a French term meaning “fatty liver”, was produced traditionally from goose and duck. Chickens are also used in the making of foie gras. The present study deals with the properties and quality of raw chicken and duck liver in comparison with manufactured liver paste (foie gras). Raw chicken liver contained 24.60% protein, 6.00% fat, 1.40 % ash, and 66.80% moisture. The average mineral values were 83.65, 50.75, 5.29, 1.15, 0.154, 0.683, 0.317 and 0.066 μg/g of Fe, Zn, Cu, Mn, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 11 publications
(11 reference statements)
2
17
1
1
Order By: Relevance
“…The protein and moisture contents of NCCLs were significantly higher than those of ANCCLs ( P < 0.01). The protein contents measured in this study for the two types of chicken livers were lower than those reported (about 24%) by Abu‐Salem and Abou Arab () and Guanru (). One reason for this may have been due to the difference in the chicken species and slaughter age compared with other studies mentioned above.…”
Section: Resultscontrasting
confidence: 84%
See 1 more Smart Citation
“…The protein and moisture contents of NCCLs were significantly higher than those of ANCCLs ( P < 0.01). The protein contents measured in this study for the two types of chicken livers were lower than those reported (about 24%) by Abu‐Salem and Abou Arab () and Guanru (). One reason for this may have been due to the difference in the chicken species and slaughter age compared with other studies mentioned above.…”
Section: Resultscontrasting
confidence: 84%
“…Therefore, there would be a large economic benefit if chicken liver could be fully utilized. Normal colored chicken livers (NCCLs) are rich in minerals, amino acids, proteins and vitamins (Abu‐Salem & Abou Arab ) and can provide a rich and economical source of many essential nutrients for humans. However, a large number of abnormal colored chicken livers (ANCCLs) are produced in large‐scale broiler breeding and slaughtering plants, possibly resulting from feeding regimens and stressful conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, poultry liver can be suffered from lipid oxidation as reported in Landes geese [3], chickens, and ducks [4]. Lipid oxidation refers to the reactive oxygen species, which exceeds the ability of a system to neutralize and eliminate them [5].…”
Section: Introductionmentioning
confidence: 99%
“…Gizzard is one of the main edible by-products of poultry processing, which is marketed as variety meats along with dressed chicken (Charoenpong and Chen, 1980). Also, chicken skin was found to be represented in range from 8 to 20% of the total carcass weight (Fereidoun et al, 2007).On the other hand, chicken liver is a rich source of essential amino acids, protein, zinc, and iron with low price cost (Abu-Salem &Abou Arab, 2010 andSeong et al, 2015). During the last decades, many studies focused on chicken meat quality evaluation and processing methods.…”
Section: Introductionmentioning
confidence: 99%